Association between Pre-Pregnancy Body Mass Index, Gestational Weight Gain, and Birth Defects, a Retrospective Study - Zhou Chu; Mingming Qi; Zaili Yu; Li Mi; Jin Long; Guohong Hu (IMR Press, 2024)
Background: To explore the correlation of pre-pregnancy body mass index (BMI) and gestational weight gain (GWG) with the occurrence of birth defects. Methods: Clinical data of pregnant women were collected in Zhuzhou Central Hospital from January 2019 to December 2021. A total of 10,086 newborns, including 175 newborns with birth defects. Birth defect cases were identified, and 350 cases of pregnant women without birth defects were randomly selected as the control group by control case matching (1:2). Clinical baseline data were compared between the two groups, and logistic single-factor analysis was performed to examine the correlation between pre-pregnancy BMI, GWG, and birth defects. Results: The study consisted of a total of 175 cases of birth defects, including circulatory system 114 (65.14%) cases, musculoskeletal system 34 (19.43%) cases, urinary system 15 (8.57%) cases, and 12 (6.86%) cases of other birth defects. There were no statistical differences in parity between the two groups (p > 0.05). However, statistically significant differences were observed in maternal age, pre-pregnancy medication history, and the perinatal TORCH (Toxoplass, Other (Syphilis, Hepatitis B), Rubivirus, Cytomegalovirus, Herpesvirus) (p < 0.05). Logistic single-factor analysis revealed that the proportion of birth defects in obese women was significantly higher than that in the control group (5.14% vs. 1.14%, p = 0.013). In the birth defect group, the distribution of inadequate, appropriate, and excessive GWG was 9.71%, 34.86%, and 55.43%, respectively. However, no statistical differences were found in the types of birth defects based on maternal BMI and GWG. Conclusion: The primary focus on addressing birth defects should center around the prevention and control of congenital heart disease. Abnormal pre-pregnancy BMI is a risk factor for birth defects. Effective control of GWG contributes to preventing adverse outcomes in newborns. Therefore, both women of childbearing age and pregnant women need to pay attention to weight management.